Phonetic comparison algorithms. - Kessler, Brett (Transactions of the Philological Society, 2005)
Appealing to phonetic similarity has traditionally been discouraged in linguistics, partly because it has been an ill-defined and subjective concept. But much research nowadays requires measures of similarity between words, from practical work in speech technology, information retrieval, and commercial branding to theoretical studies involving language comparison and history. Phonetic comparison algorithms are crucial to this work, enabling computer implementation as well as reliability and significance testing. But phonetic similarity is not a unitary concept. Various types of measures are discussed, with emphasis on those most appropriate for current and future work in historical linguistics.